Introduction to computer graphics - Zeki, Akram M. (IIUM Press, 2015)
Computer graphic represents the most recent development in improving the efficiency of communications between human beings and computers. It is used in different areas for example displaying the outcome of design and controlled computations and visualization, producing TV commercials and feature films, simulation and analysis of real-world problems, PC aided pattern, graphical end user interfaces that increases the communication bandwidth among humans and machines, and many of computers. Computer graphics is application oriented.